A Review of Gender Issues in the Dominican Republic, Haiti and Jamaica - World Bank (Washington, DC, 2013)
This report examines the effect of gender on socio-economic outcomes in three Caribbean countries: the Dominican Republic, Haiti and Jamaica. Organized in three separate country notes, it covers: demographics, health and reproductive health, violence, education, labor and agriculture. The report is part of a large effort aimed at establishing a strategic social agenda in the region. Many of the key economic issues that Caribbean countries confront today have an important gender dimension, these includes crime and violence, reproductive and sexual health issues, low education levels, unstable family structure, poverty and inequality. Gender roles and relations influence these socio-economic issues. For example, violent crime is concentrated among young men, who are both victims and offenders; domestic violence is extensive in the Caribbean sub region and for the most and for the most part involves men as the aggressors and women as the victims. Aggressive men behavior has been linked to the inability of men, mostly low income men, to meet social expectations of achieving and providing for the family, as well as to socialization patterns that teach boys to be tough and girls to be submissive. Over the long term, gender work in the three countries should continue to address socialization processes and norms that cause men and women to assume negative roles in the socio-economic stability of each country.